2021
DOI: 10.1002/ccr3.4276
|View full text |Cite
|
Sign up to set email alerts
|

Osteolytic lesions in myelofibrosis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In all 16 cases investigations revealed progressive disease (i.e., worsening fibrosis, accelerated phase MPN or AML) along with the presence of osteolytic lesions; though diagnostic procedures were often delayed until further symptoms or cytopenias developed [6][7][8][9][10][11][12][13][14][15][16][18][19][20][21]. Chambers et al reported a patient with longstanding history of PV managed with hydroxyurea who presented to her local hospital after a fall and imaging revealed the presence of an osteolytic lesion [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In all 16 cases investigations revealed progressive disease (i.e., worsening fibrosis, accelerated phase MPN or AML) along with the presence of osteolytic lesions; though diagnostic procedures were often delayed until further symptoms or cytopenias developed [6][7][8][9][10][11][12][13][14][15][16][18][19][20][21]. Chambers et al reported a patient with longstanding history of PV managed with hydroxyurea who presented to her local hospital after a fall and imaging revealed the presence of an osteolytic lesion [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In total, 16 case reports were found, highlighting that osteolytic lesion secondary to MPNs is rare (Table 1 ) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. All patients reported new or worsening bone pain as a presenting symptom.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations